(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
The article reveals the essence and content of inclusive education, substantiates the need to improve the mechanisms of methodological competence of primary school teachers. A scientific and theoretical analysis of various approaches to the organization of pedagogical activity of primary school teachers in working with special children is given, the concept of "professional competence" is revealed. The structure of the inclusive-methodical competence of a primary school teacher is presented, including personal-value, information-knowledge, activity, evaluative-analytical components